Cranial CT is a mandatory tool to exclude asymptomatic cerebral hemorrhage in elderly patients on anticoagulation - Schindler, Cora R.; Best, Alicia; Woschek, Mathias; Verboket, René D.; Marzi, Ingo; Eichler, Katrin; Störmann, Philipp (Frontiers in Medicine, 2023)
Background Traumatic brain injury (TBI) after falls causes death and disability with immense socioeconomic impact through medical and rehabilitation costs in geriatric patients. Diagnosing TBI can be challenging due to the absence of initial clinical symptoms. Misdiagnosis is particularly dangerous in patients on permanent anticoagulation because minimal trauma might result in severe intracranial hemorrhage. The aim of this study is to evaluate the diagnostic necessity of cranial computed tomography (cCT) to rule out intracranial hemorrhage, particularly in the absence of neurologic symptoms in elderly patients on permanent anticoagulation in their premedication. Patients and methods Retrospective cohort analysis of elderly trauma patients (≥ 65 years) admitted to the emergency department (ED) of the level-1-trauma center of the University Hospital Frankfurt from 01/2017 to 12/2019. The study included patients who suffered a ground-level fall with suspected TBI and subsequently underwent CT because of preexisting anticoagulation. Results A total of 227 patients met the inclusion criteria. In 17 of these patients, cCT showed intracranial hemorrhage, of which 14 were subdural hematomas (SDH). In 8 of the patients with bleeding showed no clinical symptoms, representing 5% (n = 160) of all symptom-free patients. Men and women were equally to suffer a post-traumatic hemorrhage. Patients with intracranial bleeding were hospitalized for 14.5 (±10.4) days. Acetylsalicylic acid (ASA) was the most prescribed anticoagulant in both patient cohorts—with or without intracerebral bleeding (70.6 vs. 77.1%, p = 0.539). Similarly, patients taking new oral anticoagulant (NOAC) (p = 0.748), coumarins, or other platelet inhibitors (p > 0.1) did not show an increased bleeding incidence. Conclusion Acetylsalicylic acid and NOAC use are not associated with increased bleeding risk in geriatric trauma patients (≥ 65 years) after fall-related TBI. Even in asymptomatic elderly patients on anticoagulation, intracranial hemorrhage occurs in a relevant proportion after minor trauma to the head. Therefore, cCT is an obligatory tool to rule out cerebral hemorrhage in elderly patients under anticoagulation.